Madagascar : Promoting Livestock Production - Mohan, Prasad C. (2012)
The note outlines the successful outcomes of the Livestock Adjustment and Investment Project in Madagascar, whose main objective was to promote livestock production for domestic consumption, and exports. A major project impact, i.e., the Ministry of Livestock's shift out of veterinary practice, - feed mill operation, fodder production, input supply, and breed improvement - was conducive to service contracts, and the establishment of a private veterinary profession, which significantly improved performance, as confirmed by subsequent reviews. Moreover, extension programs were successfully developed in support of farmers' associations, improved crop varieties were adopted, and significant progress was made with genetic improvement, and research and development. Lessons reinforce the importance of government commitment towards divestiture, particularly concerning privatization, emphasizing that the absence of commitment to policy adjustment, should deter project implementation. More importantly, policy reforms should complement institutional development and investments, where good roads and credit access are particularly important for rural, and private development, while investments in these areas may be sub-optimal in Bank lending.